Martin Luther's Critique of Supererogation - Walker, John (Journal of religious ethics, 2025)
Recent decades have witnessed a surge of philosophical interest in the concept of supererogation. Although Martin Luther figures prominently in the historiography as a critic of supererogation, the particular nature of his critique and its place within his broader moral theology has been underexplored. This article offers a reconstruction of Luther's theological opposition to supererogation, demonstrating its tight connection to central elements of his spiritual and ethical vision. Three elements are identified and discussed: the relationship between faith and the Word of God, the distinction between divine and human law, and the equality of Christian vocations within the community of believers. The article concludes by suggesting the ongoing relevance of Luther's antisupererogationism for contemporary religious ethics.